The Abolition of GST Under New Malaysia - Asriezam Uda, Asriezam Uda; Fauziah Ani, Fauziah Ani (HRMARS, 2023)
The implementation of the Goods and Services Tax (GST) was met with strong opposition from Malaysians leading to the fall of the Barisan Nasional Government in the 14th General Election and the abolition of GST. Past studies have shown that the abolition of GST is a less wise move because there is a greater negative impact compared to the positive impact on the economy, society, and country. The present study was conducted to investigate the importance of GST on national income, the factors of GST repeal, as well as the impact of the abolition of GST on people's purchasing power. Issues related to the abolition of GST were raised following people's complaints about the implementation of the Sales and Service Tax (SST) system which is found to be less impactful in contrast to the people's expectations before the repeal of GST is implemented. Qualitative methods were used in the form of interviews, journal references, related articles, book reports, and statistical data from the Department of Statistics Malaysia and the Malaysian Ministry of Finance. The data gathered were used to further clarify the impact of the implementation of the political policy of the Pakatan Harapan (PH) Government for an economic purpose as well as benefiting the people. The theory of People's Sovereignty is used in this research. The results of the study show that GST plays a role as the biggest contributor in the component of Indirect Taxes (IT) until its abolition which no longer contributes to national income. Even though the Malaysian government opted for other methods of increasing revenue such as increasing income tax, the dependence on individual income tax increases as a result of decreasing people's purchasing power based on the Consumer Price Index (CPI). The main external factor identified was due to traders who maximized their profits which subsequently contributed more to the increase in the price of goods, followed by weak law enforcement by the authorities making GST the victim of political populists. From the perspective of political sciences, the present study also revealed how the government’s policy based on politics gives an impact on the economy and society.